Analisis Strategi Pemasaran KFC Dengan Pendekatan SWOT Dan Marketing Mix 7P - Nabila Ramadhania; Siti Fatimah; Romasta Juli Novalia Manurung; Lasahuf Rasyid Ridho; Ahmad Rifai Arif; Husni Mubarok (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze KFC's marketing strategy using a SWOT approach and the 7Ps Marketing Mix to face competition in the fast food industry in Indonesia. The study used a quantitative descriptive method with data collected through a questionnaire from 60 KFC Zambrud consumers. The results indicate that the Place dimension is KFC's main strength due to its strategic and accessible location, while the Promotion dimension is a weakness that needs the most improvement. The SWOT analysis identified key opportunities in the form of the growth of app-based delivery services and the development of digital marketing, while the greatest threats come from local competitors and changing trends in healthy eating. This study concludes that KFC's business sustainability requires a more creative integration of physical strengths and digital promotional strategies. The results of this study are expected to serve as evaluation material for KFC management and as an academic reference in the study of marketing strategies in the fast food industry.